Antibacterial activity of plant extracts commonly used as folk medicines collected from National Parks in Jambi, Indonesia - Hanif, Addienda Muhammad; Endah , Retnaningrum; Yekti , Asih Purwestri; Laurentius , Hartanto Nugroho (Plant Science Today, 2025)
The local communities in Jambi used medicinal plants collected from national parks, such as Calamus manan, Helminthostachys zeylanica and Zingiber montanum, to treat illnesses. This study aims to evaluate the antibacterial activity of C. manan, H. zeylanica and Z. montanum against reference strains of Escherichia coli [ATCC 25922], Pseudomonas aeruginosa [ATCC 15442] and Staphylococcus aureus [ATCC 6538]. The assessment was conducted using disc and agar well diffusion methods, where all plant extracts showed antibacterial activity against the tested bacteria. Chloroform extract of C. manan (CMC) stems had the most significant growth inhibition zone against all reference strains for both methods. Specifically, the disc and agar well diffusion values of CMC extract observed against S. aureus were 17.67 mm and 22.00 mm respectively. MIC determination also indicated that CMC extract possesses the most significant antibacterial activity, with the lowest value observed against S. aureus at 0.312 mg/mL. The SEM results also showed the damage to the morphology and structure of S. aureus cells, especially the damaged cytoplasmic cell walls and membranes. The GC-MS analysis identified 30 different compounds from the CMC extract, with 4,5-dimethyl-1-hexene and terpineol-4 being the main components. These compounds are known for their potential as antimicrobial, antioxidant and anti-inflammatory agents. Considering these results, it was concluded that Jambi medicinal plants, particularly C. manan, exhibit antibacterial activities and contain secondary metabolites that may serve as a potential source of antibacterial compounds.